2008
DOI: 10.1016/j.schres.2008.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms are associated with less alcohol use, craving, and “high” in alcohol dependent patients with schizophrenia

Abstract: Background-Alcohol use disorders (AUDs) frequently co-occur with and exacerbate schizophrenia, yet the specific relationships between schizophrenia symptoms and alcohol use remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…cognitive, social, affective, and communicative). This is in line with findings linking alcohol dependence attributes such as craving with global psychiatric symptom severity (Batki et al, 2008). Along with the greater degree of EPS after controlling for medication status (Potvin et al, 2006b), it may also explain the associated medication non-compliance we found, consistent with previous research (Buckley, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…cognitive, social, affective, and communicative). This is in line with findings linking alcohol dependence attributes such as craving with global psychiatric symptom severity (Batki et al, 2008). Along with the greater degree of EPS after controlling for medication status (Potvin et al, 2006b), it may also explain the associated medication non-compliance we found, consistent with previous research (Buckley, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Among this population alcohol misuse has been linked to a range of adverse consequences including unemployment, lower education level and lower socioeconomic status 2. Studies examining the impact of alcohol misuse on various psychiatric symptoms among people with psychotic disorders report inconsistent findings 3 4…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…The most consistent finding within this phase of the illness is that AUDs are associated with increased positive symptoms (e.g., paranoia and auditory hallucinations), thought disorganization and depression [40,47,[74][75][76][77][78][79]. Furthermore, Swendsen and colleagues monitored substance use and positive symptoms in real time and found that cannabis use preceded positive symptoms and anxiousness, while alcohol use tended to follow eruptions of positive symptoms and anxiousness [80].…”
Section: Psychopathologymentioning
confidence: 99%
“…AUDs have also been associated with both greater [81] and lesser amounts [74,82] of negative symptoms.…”
Section: Review Smith and Csernanskymentioning
confidence: 99%
See 1 more Smart Citation